2016
DOI: 10.1519/jsc.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Positional Match Running Performance in Elite Gaelic Football

Abstract: km.h -1 . Players completed 184 ± 40 accelerations which represent 2.6 ± 0.5 a.min -1 . There were significant differences between positional groups for both total running distance, high speed running distance and sprint distance, with midfielders covering more total and high speed running distance, compared to other positions (p<0.001). There was a reduction in high speed and sprint distance between the first and second half (p<0.001). Reductions in running performance were position dependant with the middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 37 publications
(65 reference statements)
8
85
3
2
Order By: Relevance
“…Such results may relate to the variation of physical demands across playing positions. For instance, high-speed distance (>17 km hour) is reportedly lower for forwards (18.2 m/min) than defenders (22.5 m/min) or midfielders (31.8 m/min) 2. The large 95% CI IRR observed for goal keepers (1.4; 95% CI 0.63 to 3.17) may reflect a small sample size or unique physical–technical demands.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such results may relate to the variation of physical demands across playing positions. For instance, high-speed distance (>17 km hour) is reportedly lower for forwards (18.2 m/min) than defenders (22.5 m/min) or midfielders (31.8 m/min) 2. The large 95% CI IRR observed for goal keepers (1.4; 95% CI 0.63 to 3.17) may reflect a small sample size or unique physical–technical demands.…”
Section: Discussionmentioning
confidence: 94%
“…Match play is characterised by intermittent bouts of multidirectional running as elite players reportedly cover 8889 m, with 18% at a high-speed pace (>17 km/hour) 2. Two opposing teams of 14 outfield players and a goalkeeper play on a grass pitch 145 m long by 90 m wide 1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified sports such as soccer, baseball and ice hockey as sports commonly associated with FAI [18][19][20][21] . While the majority of sportsmen in both study groups included in this research were athletes participating in the Irish national sports of Hurling and Gaelic football; these sports are multidirectional, high intensity field sports 22 similar to rugby, soccer and hockey (the other sports in this study) in terms of distances covered and movement patterns required [23][24][25] and therefore likely represent the risk posed to other field sports athletes. Children may participate in organised and structured training for the Gaelic games as early as the "under-6" age category with their club.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancement in technology has improved the ease to which locomotion data collection can take place. There has been an increase in monitoring of the external training load in match and training situations through the use of global positioning satellite systems (GPS) (Casamichana et al, 2014, 2015; Evans et al, 2015; Malone et al, 2015). The advent of this technology has resulted in total distance covered and distance covered at arbitrary demarcated thresholds of high speed locomotion being utilised to quantify the TL.…”
Section: Introductionmentioning
confidence: 99%